Il corpus dei testi medievali sardi: una presentazione riassuntiva - Fodor, Andrea (Verbum – Analecta Neolatina, 2012)
This paper describes the corpus of texts written in Sardinian in the period of the giudicati (11th–15th century). The corpus consists mainly of legal documents (donations, litigations, statutes) and a chronicle (Libellus Judicum Turritanorum). They make use of the local varieties of Sardinian, showing a division of logudorese, campidanese and arborense dialects. The need for an updated philological revision has been met by recent editions of several important documents, making it possible to use these for further linguistic research about the structure of medieval Sardinian.